Morphometric analysis of clinically significant parameters of the main trunk of the left coronary artery - Almira Lujinović; Lejla Dervišević; Zurifa Ajanović; Dina Kapić; Azra Metović; Esad Ćosović; Maida Šahinović; Jasmin Mušanović; Jelena Kovačević-Prstojević; Esad Pepić (Medicinski glasnik, 2023)
Aim: To determine the value of angles between the left coronary artery main trunk (LMT) and its branches, the anterior interventricular branch (LAD) and the circumflex branch (CX), and their possible relationship with the LMT length. Methods: A total of 29 cadaveric hearts were used. The left coronary artery and its branches were dissected. The hearts were then classified according to the number of branches. The LMT length was measured with a digital gauge, and the LAD-CX angle, LMT-LAD angle and LMT-CX angle with a manual goniometer. Results: The average value of the LMT length was 9.0 mm (6.0-13.5). In 20 (68.97%) samples, the LMT was divided into two terminal branches. There was no statistically significant difference (p=0.321) in LMT length between the hearts with a bifurcation and without it. The average value of the LAD-CX angle was 89.0⁰ (74.5-93.0), with a statistically significant difference (p=0.020) comparing to hearts with trifurcation. The mean value of the LMT-LAD angle was 30.83±9.23⁰ and it was significantly lower (p=0.006) in the group of hearts with bifurcation compared to the group with trifurcation of the main trunk. Conclusion: The LMT length shows great variability and is not related to the LAD-CX, LMT-LAD or the LMT-CX angle. Knowledge of the left coronary variation is essential in order to avoid misinterpretation of arteriogram.
Keywords: anatomical variations; branching pattern; left coronary artery